2003
DOI: 10.1002/cne.10784
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a cone bipolar cell in cat retina which has input from both rod and cone photoreceptors

Abstract: It has been generally accepted that rod photoreceptor cells in the mammalian retina make synaptic contact with only a single population of rod bipolar cells, whereas cone photoreceptors contact a variety of cone bipolar cells. This assumption has been challenged in rodents by reports of a type of cone bipolar cell which receives input from both rods and cones. Questions remained as to whether similar pathways are present in other mammals. We have used an antiserum against the glutamate transporter GLT1-B to vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 42 publications
(63 reference statements)
4
24
0
Order By: Relevance
“…These findings argue for direct input from rods into the cone pathway referred to as the alternative rod pathway. In several species anatomical evidence for sparse synapse-like contacts from rods to OFF cone bipolar cells has been published (Hack et al, 1999Tsukamoto et al, 2001;Fyk-Kolodziej et al, 2003;Li et al, 2004, Mataruga et al, 2007. This connection could provide the anatomical basis for the alternative rod pathway.…”
Section: Alternative Rod Pathwaymentioning
confidence: 94%
See 1 more Smart Citation
“…These findings argue for direct input from rods into the cone pathway referred to as the alternative rod pathway. In several species anatomical evidence for sparse synapse-like contacts from rods to OFF cone bipolar cells has been published (Hack et al, 1999Tsukamoto et al, 2001;Fyk-Kolodziej et al, 2003;Li et al, 2004, Mataruga et al, 2007. This connection could provide the anatomical basis for the alternative rod pathway.…”
Section: Alternative Rod Pathwaymentioning
confidence: 94%
“…One route signals through gap junctions between rod spherules and cone pedicles (DeVries and Baylor, 1995). In the other route, rods are directly connected with OFF cone bipolar cells (Soucy et al, 1998;Hack et al, 1999Hack et al, , 2001Tsukamoto et al, 2001;Fyk-Kolodziej et al, 2003;Li et al, 2004;Mataruga et al, 2007). However, the impact of this alternative pathway on transmission seems to be species dependent (Protti et al, 2005).…”
mentioning
confidence: 96%
“…Direct rod to OFF cone bipolar cell connections have also been described in rat, cat, and rabbit retina (Hack et al, 1999;Fyk-Kolodziej et al, 2003;Li et al, 2004;Protti et al, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…1C). Subsequent studies showed that rods make chemical synapses with OFF cone bipolar cells (Hack et al, 1999;Tsukamoto et al, 2001;Fyk-Kolodziej et al, 2003;Li et al, 2004). It is presently unclear whether rod-driven OFF signals use two or three distinct pathways.…”
Section: Introductionmentioning
confidence: 99%